Sistem Informasi Akademik Berbasis Web Menggunakan Metode Pengembangan Sistem Extreme Programming - Arafat, Muhamad Yasser; Yoga Putra Pratama (Jurnal Informatika Universitas Pamulang, 2024)
In the field of education, communication among educational staff, teachers, students, and parents significantly influences the success of the learning process. Smooth communication, delivery, and processing of information are essential needs. The use of technology is expected to accelerate and improve the accuracy of these processes. However, the application of information technology in many schools remains limited. Academic data management processes, such as student, teacher, grade, and attendance records, are often still carried out manually or using Microsoft Excel. Unfortunately, the use of Excel is not optimal as it lacks an integrated database system. This study aims to address the challenges faced by Madrasah Aliyah Andalusia by designing an academic website application using the Extreme Programming method. This method enables faster system development and greater flexibility in responding to changes. The website application allows administrators, teachers, and students to easily access data such as grades, schedules, subjects, and other information. This system is expected to improve the efficiency of academic data management and support the smooth running of educational processes in schools.